2013
DOI: 10.1186/1471-2407-13-495
|View full text |Cite
|
Sign up to set email alerts
|

Phase I drug-interaction study of effects of calcium and magnesium infusions on oxaliplatin pharmacokinetics and acute neurotoxicity in colorectal cancer patients

Abstract: BackgroundCalcium and magnesium (Ca/Mg) infusions have been suggested as an effective intervention for preventing oxaliplatin-induced neurotoxicity, but the effects of Ca/Mg infusions on oxaliplatin pharmacokinetics, motor nerve hyperexcitability and acute neurotoxicity symptoms are unclear.MethodsIn this double blind crossover study, colorectal cancer patients undergoing oxaliplatin-based chemotherapy were randomised to receive Ca/Mg (1g Ca Gluconate plus 1g MgSO4) on cycle 1 and placebo (vehicle alone) on cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…For instance, calcium and magnesium (Ca/Mg) infusions were recommended as an effective method to reduce oxaliplatin-induced neurotoxicity, 58 but recent phase I and II studies demonstrated that Ca/Mg infusions did not seem to prevent acute neurotoxicity of oxaliplatin. 57,58 In addition, the biotransformation in the bloodstream also contributes to the side effects of platinum (II) complex. 59 For example, Sooriyaarachchi et al focused on the mechanism of sodium thiosulfate (STS) modulated metabolism of cisplatin in human plasma in vitro.…”
Section: Challenges Of Platinum (Ii) Complex Drugsmentioning
confidence: 99%
“…For instance, calcium and magnesium (Ca/Mg) infusions were recommended as an effective method to reduce oxaliplatin-induced neurotoxicity, 58 but recent phase I and II studies demonstrated that Ca/Mg infusions did not seem to prevent acute neurotoxicity of oxaliplatin. 57,58 In addition, the biotransformation in the bloodstream also contributes to the side effects of platinum (II) complex. 59 For example, Sooriyaarachchi et al focused on the mechanism of sodium thiosulfate (STS) modulated metabolism of cisplatin in human plasma in vitro.…”
Section: Challenges Of Platinum (Ii) Complex Drugsmentioning
confidence: 99%
“…Results of several recent randomized clinical trials testing the effectiveness of calcium/magnesium infusion to counteract acute OHP neurotoxicity are available [ 93 , 94 , 95 ].…”
Section: Main Mechanisms Of Platinum Drug Neurotoxicitymentioning
confidence: 99%
“…Despite a theoretical basis for the use of this kind of neuroprotection, the overall results and in particular the two most recent trials [ 94 , 95 ] failed to demonstrate a real protection of calcium/magnesium infusion in acute OHP neurotoxicity.…”
Section: Main Mechanisms Of Platinum Drug Neurotoxicitymentioning
confidence: 99%
“…To mimic clinically achievable oxaliplatin exposures in vitro, cells were treated for 3 h with 10, 30 and 100 lM oxaliplatin. Considering the rate of oxaliplatin degradation in supplemented Neurobasal-A medium (t 1/2 % 3 h; Figure S1), determining by HPLC (Ip et al 2008), these in vitro treatments equated to AUCs for oxaliplatin exposure of 21.7, 65 and 217 lM.h, respectively, or to those achieved after 1.5, 4.3 and 14 standard clinical doses of oxaliplatin chemotherapy (85-130 mg/m 2 ) respectively (Han et al 2013). Representative images suggested the presence of Fig.…”
Section: Effects Of Oxaliplatinmentioning
confidence: 99%
“…To investigate this hypothesis, we established a click chemistry 5-ethynyluridine (EU) RNA incorporation fluorescence labelling assay to visualize and measure global transcriptional activity (Jao and Salic 2008) in individual DRG neurons in vitro, and related these measurements to those of neuronal cell body size. Cultured DRG cells were treated with oxaliplatin and other platinum drugs using in vitro experimental conditions mimicking clinically achievable chemotherapy drug systemic exposures (Han et al 2013). Effects of in vitro treatment with platinum drugs on DRG neuronal size and global transcriptional activity were related to levels of platinum DNA binding, measured by inductively coupled plasma mass spectrometry (Brouwers et al 2008).…”
mentioning
confidence: 99%